Health care cost reduction by controlling the number of hospital outpatients in Japan - ITO, ATSUSHI (Advances in Social Sciences Research Journal, 2016)
The Japanese government provides universal health coverage and allows all citizens free access to medical services. Because of this, many patients tend to visit hospitals rather than clinics, thus wasting health care resources. This study analyzed the effects of controlling the number of hospital outpatients on reductions in outpatient health care costs. I estimated the reduction achieved if 80% of outpatients are treated in clinics. The results offer two major findings. 1) Though 72% of outpatients were visiting outpatient clinics, the hospital outpatient health care cost accounted for approximately 40% of total outpatient health care costs; the health care cost per 10 thousand outpatients was 1.8 times higher in hospitals than in clinics. 2) The estimated cost reduction if 80% of outpatients were treated in clinics was approximately 707.3 billion yen, accounting for 5% of total outpatient health care costs. If this is achieved, an additional approximately 368 thousand outpatients can be treated in clinics, and increases in health care costs can be slowed. Therefore, reducing the number of outpatients in hospitals can help make the allocation of health care resources more efficient.